2021
DOI: 10.3390/foods10071533
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Coumarins and Furocoumarins through Citrus Beverages: A Detailed Estimation by a HPLC-MS/MS Method Combined with the Linear Retention Index System

Abstract: Official regulations concerning the maximum number of substances in food are introduced as a consequence of possible adverse effects, after oral administration. In this regard, analytical methods are necessary in order to determine specific targets. Among oxygen heterocyclic compounds (OHCs, that are furocoumarins, coumarins and polymethoxyflavones), only coumarin is subject to restriction by the Regulation (EC) No 1334/2008 of the European Parliament. Furocoumarins are known for their phototoxicity and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…CGLs are potentially toxic for humans and result in acute cyanide intoxication, high respiration rate, lower blood pressure, headache, dizziness, stomach pains, diarrhea, vomiting, and mental confusion. , Furocoumarins are found in many plants including carrots, celery roots, citrus fruits, parsley, and citrus plants. These compounds are responsible for gastrointestinal ailments and phototoxicity, skin reactions under UV light. , Lectins are reported from beans like kidney beans and can result in stomachache, diarrhea, and vomiting …”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%
“…CGLs are potentially toxic for humans and result in acute cyanide intoxication, high respiration rate, lower blood pressure, headache, dizziness, stomach pains, diarrhea, vomiting, and mental confusion. , Furocoumarins are found in many plants including carrots, celery roots, citrus fruits, parsley, and citrus plants. These compounds are responsible for gastrointestinal ailments and phototoxicity, skin reactions under UV light. , Lectins are reported from beans like kidney beans and can result in stomachache, diarrhea, and vomiting …”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%
“…Occurrence : Psoralen (7H-furo[3,2-g][ 1 ]benzopyran-7-one) ( Figure 1 (12)) is a furocoumarin which is naturally present in several plants, notably Psoralea corylifolia , celery, parsley and in all citrus fruits, including bergamot orange peel, whose oils are used as flavors [ 214 , 215 , 216 , 217 ]. In citrus-flavored beverages, the highest levels of psoralens, 29 and 24 mg/L, were found in bergamot juice and home-made limoncello, respectively [ 218 ]. Levels of psoralens in celery varied, depending on when it was harvested, from 26 to 84 μg/g fresh weight [ 216 ].…”
Section: Dna-reactive Carcinogens and Related Chemicals Present In Foodmentioning
confidence: 99%
“…Finally, Arigò et al [ 154 ] reported the use of LC-MS/MS combined with the linear retention index system as an innovative analytical strategy for the characterization of 35 oxygen heterocyclic compounds that include furocoumarins, coumarins and polymethoxyflavones, in Italian citrus beverages. In that study, 19 furocoumarins were considered.…”
Section: Furocoumarinsmentioning
confidence: 99%